Project Based Learning Model to Improve Students' Critical Thinking Skills in Natural Science Learning at MIS Asy Syafi'iyah Pecangakan - Fitrianingsih, Uun; Rahmawati, Wahidah; Hasanah, Uswatun; Khasanah, Uswatun; Rosyida, Vina Nur (DEEP LEARNING: Journal of Educational Research, 2025)
The 21st century life is a life without boundaries, globalization, and the exploration of technology is very easy. The digital economy era of the 21st century requires a knowledgeable, skilled, and innovative workforce. Therefore, students must be able to solve problems with superior thinking ability to be ready to plunge into global society. To overcome this challenge, students need to be equipped with 21st century skills that have four main components: digital literacy skills, creative thinking, effective communication skills, and high productivity. In these four components, critical thinking skills are included in the thinking component of creativity. The ability to think critically is very important for students to solve problems that arise with logical reasoning and appropriate solutions. To develop critical thinking skills, it is necessary for teachers to create appropriate learning strategies in schools that contains four pillars of education established by UNESCO: learning to know, learning to do, learning to live together and learning to be. Based on the four pillars, the project based learning model is appropriate to develop student’s critical thinking skills. This is because in the model, students as learning center are given a project-shaped problem and they are required to solve it.